PENYELENGGARAAN PERIZINAN MELALUI ONLINE SINGLE SUBMISSION (OSS) PADA DPM-PTSP KABUPATEN GOWA PERSPEKTIF SIYASAH SYAR’IYAH - Wijaya, Moh. Ramlan; Risal, Chaerul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This study aims to determine the procedures for using the Online Single Submission (OSS) system and the impact on society based on the perspective of Siyasah Syariah at the Investment and One-Stop Service Office of Gowa Regency, while the issues raised are the licensing mechanism through the Online Single Submission (OSS) system and the impact accepted by society from the point of view of Siyasah Syar’iah. The research uses normative syar’I and normative juridical research approaches, qualitative descriptive research types, research locations in DPM-PTSP Kab. Gowa, secondary data sources in the form of literature such as journals, thesis books and primary data in the form of interviews, observation and documentation, techniques and processing used display, editing, reduction, analysis and conclusions. The findings obtained are, Licensing through the OSS system at PTSP Kab. Gowa has shown a positive impact on the community, both in terms of procedures for using the system and the benefits obtained by the community with the system, which illustrates that it has been running well in accordance with the service principles of simplicity and convenience, so that this is in accordance with what is contained in several concepts. Siyasah Syar’iyah, namely maslahah mursalah and maslahah al-’ammah regarding the formation of government policies must provide benefits for the whole community